Bunch characteristics of an electron beam generated by a diamond secondary emitter amplifier - Jensen, Kevin L.; Yater, Joan E.; Shaw, Jonathan L.; Myers, Robert E.; Pate, Bradford B.; Butler, James E.; Feygelson, Tatyana (Journal of applied physics, 2010)
Electron bunches for high performance free electron lasers are subject to constraints on charge per bunch and pulse shape. A Diamond secondary emitter used in conjunction with a photocathode and drive laser has potential to enable a high brightness, high peak current photoinjector by increasing the effective quantum efficiency of the photocathode. A theoretical characterization of the bunches so produced has been heretofore absent. Using a combination of Monte Carlo and analytical models, the shape of the bunches, their transit time, and emission time constants are determined and shown to be sensitive to the accelerating field in the diamond flake, incident beam profile, doping, and surface conditions. Methods to allow for extension to regimes of technological interest in terms of diamond thickness, external field, and primary pulse shape are given.